The effect of transition-action-details technique on the narrative writing of the eighth grade students of junior high school - I Gede Susila Darma Darma; Mas Arya Suwardana (PT. MAWAMEDIA JAYAMUSTA BUANASIHA, 2024)
This study was an experimental research which aimed at determining the effect of Transition-Action-Details technique on the narrative writing competency of the eighth-grade students of SMP. The sampling technique that was used in this study was cluster random sampling through lottery. The lottery was given twice. The result of the first lottery indicated that class VIII.B and class VIII.C were selected as the samples of this study. Both of the samples consisted of 25 students. The result of second lottery indicated that class VIII.B was assigned as experimental group who were taught by using Transition-Action-Detail technique and class VIII.C was assigned as control group who were taught by using conventional writing technique. Research design of this study was Post-test only control group design. After conducting post-test, the result was analysed descriptively and inferentially. The result of data analysis showed that the students who were taught by using Transition-Action-Details technique performed better achievement than those who were taught by using conventional writing technique. It had been proved from the mean score of the experimental group was 82.60 while the score of control group was 73.32. Moreover, the result of t-test analysis was 4.381. In which the comparison was (4.381 > 1.96) tob = 4.381 is higher than tcv = 1.96 in the level significance 0.05. It indicates that there is a significant difference between the two groups’ score. In this case, null hypothesis (Ho) in this study was rejected. It can be concluded that Transition-Action Detail technique contributed significant influence to the students’ writing competency. It can be noticed that the students in the experimental group obtained better result than the students in control group.